TANGGUNG JAWAB SOSIAL PERUSAHAAN HAUS! INDONESIA DALAM MENINGKATKAN LOYALITAS KONSUMEN SAAT MARAKNYA AKSI BOIKOT - Andreani, Elina Felda; Firdaus, Firdaus; Nurhayati, Nurhayati; Ayu, Nadia (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
Haus! Indonesia serves variety food and beverages and increasing sales every year, unfortunately in making a menu there are raw materials from product that are currently boycotted so that is becomes a challenge for Haus! Indonesia in increasing customer loyalty. Customer trust and customer engagement through corporate social responsibility can be effort to increase customer loyalty. This study purposes to test the mediating effect of corporate social responsibility to increase customer loyalty. This study use quantitative methods. Data was collated using questionnaires and analysis data using SEM-PLS including validity test, reliability test, direct effect test, and mediation test. The result are trust, customer engagement has a direct and significant positive effect customer loyalty, corporate social responsibility. Our new finding are corporate social responsibility does not intermediate customer trust on customer loyalty, but corporate social responsibility mediates customer engagement and customer loyalty. The conclusion is to increase customer loyalty, Haus! Indonesia needs to take corporate social responsibility to reduce the risk of using boycotted materials.